Euterpe music therapy method for children with cerebral palsy - Liuzzi, Tommaso; Bompard, Sarah; Raponi, Massimiliano; D’Arienzo, Fiammetta; Staccioli, Susanna; Napoli, Eleonora; Diotallevi, Martina Frascari; Piga, Simone; Giuliani, Roberto; Castelli, Enrico (Frontiers in Neurology, 2024)
Introduction The main purpose of our study was to evaluate whether involvement in a personalized music therapy program (Euterpe method), could improve the condition of children with cerebral palsy and their parents, compared to a control group. It investigated whether it could positively affect children’s sleep quality, temperament and quality of life, quality of family life, and parental stress. Methods A prospective single-center experimental study was conducted at “Bambino Gesù” Children’s Hospital (Rome, Italy). All subjects involved attended an intensive rehabilitation program in the Neurorehabilitation Unit. In a group of patients (n = 25), a music therapy treatment was applied to evaluate the effect before and after the intervention. This group was also compared with a control group (n = 10) undergoing a standard protocol without music therapy. Results In the experimental group, the analysis shows statistically significant effects in the Disorders of initiating and maintaining sleep (p = 0.050) and the Sleep wake transition disorders (p = 0.026) factors, and the total score (p = 0.031) of Sleep Disturbances Scale for Children; the Positive emotionality scale (p = 0.013) of Italian Questionnaires of Temperament (QUIT); the Emotional Functioning (p = 0.029), Social Functioning (p = 0.012), Worry (p = 0.032), Daily Activities (p = 0.032), Total Score (p = 0.039) and Parent HRQL Summary Score (p = 0.035) dimensions of Pediatric Quality of Life for family. While in the control group, only the Attention scale of QUIT (p = 0.003) reaches statistical significance. Discussion Our study suggests that music therapy with the Euterpe Method has beneficial effects on fundamental aspects of the child’s and his parents’ lives, such as sleep, emotion control, and quality of family life.